Identification of Compounds and Antidiabetic Activities of the Ethyl Acetate Fraction of Yacon (Smallanthus sonchifolius) Leaves using In Silico and In Vitro Approaches - Pratama, Binar; Irianti, Tatang; Purnomo, Hari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Yacon (Smallanthus sonchifolius) is a plant that is vastly cultivated in Indonesia and has anti-diabetic activity. The purpose of this study was to isolate the compounds from the semipolar fraction of yacon leaves, as well as test them in silico and in vitro approaches. In this study, we use maceration for extraction, fractionation with n-hexane and ethyl acetate as solvent, and separation by preparative TLC method. The compounds tested were in silico by molecular docking using plant applications and in vitro by alpha-glucosidase inhibition assay. The difference between the molecular docking scores of an obtained molecule was calculated with Pair T-test methods. The results of the separation of the ethyl acetate fraction yielded a fraction, namely the H fraction. GC-MS analysis and IR spectroscopy showed that the H fraction contained the dominant compound called phthalic acid, di(2-propyl pentyl) ester. The docking score of the phthalic acid di(2-propyl pentyl) ester molecule and the alpha-glucosidase receptor, it is showed lower potency than 1-deoxynojirimycin as an alpha-glucosidase inhibitor. The in vitro test results showed that isolate H (IC50 = 130.479 ppm) from yacon leaves was no better than acarbose as an alpha-glucosidase enzyme inhibitor because the IC50 value was > 100 ppm.